Assembling a Three‐Dimensional Computed Tomography Database. (23rd August 2013) - Ho, Brian; Solares, C. Arturo
Abstract : Objectives: It is important for surgery to keep up with new technologies. Current skull‐base techniques use stereotactic navigation, assisted by magnetic resonance (MRI) and computed tomography (CT) compilation. Our objective is to assemble a normalized CT database for three‐dimensional (3D) endocranial renderings. This database can provide preoperative information for assistive mapping and intraoperative land marking during procedures. Methods: 222 CT studies were pooled between October 2011and December 2012. These studies were then deidentified and loaded into third party software, Osirix (Pixmeo, Switzerland), and reconstructed into 3D renderings. The Osirix program is a freeware‐based Apple‐only‐program capable of volumetric analysis, metrics, and 3D space manipulation. The database was then encrypted for patient information protection. Results: A total of 179 studies(101 males and 78 females) were ultimately used. Two‐hundred gigabytes of hard‐disk space was used. An Apple (Cuptertino, CA) laptop, running Mac OSX, was used for computation. The Osirix software was downloaded as freeware, requiring no payment. The hard‐disk was purchased at a local electronics store for $100.00 USD. The computer was approximately $1300. Conclusions: Radiologic imaging drives preoperative surgical planning. This can be augmented by new technology and creative applications of current innovations. There has not been an explanation process on how to assemble this data for departments and individuals. We provide a simple, reproducible, and inexpensive guide to CT head databases. Once the database is assembled, it may be used for such projects as mapping the parapharyngeal carotid, estimating endocranial volumes, and surgical diagrams.